Ultrasonic-Assisted Surface- Modification of Nanosilica Chloride and its Use for Synthesis of 3,4- Dihydropyrimidinones - Tajbakhsh, Mahgol; Ranjbar, Yousef; Masuodi, Abdolhosein; Rezaee, Parizad; Tajbakhsh, Mahmood; Fallah, Zari (Letters in Organic Chemistry, 2014)
Nanosilica chloride was prepared with modification of the surface by applying ultrasonic irradiation and has been employed as an efficient, heterogeneous and effective catalyst in the preparation of 3,4- dihydropyrimidinones (DHPMs) under solvent-free conditions. Simple workup procedure, short reaction time, and good to excellent yield of the product, are other advantages of this catalyst.
Keywords: heterogeneous catalyst